2007
DOI: 10.1007/s11211-007-0040-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship Between Racial Prejudice and Support for the Death Penalty: The Racist Punitive Bias Hypothesis

Abstract: Many studies have shown that there are significant racial disparities in the application of death penalties. In this paper, three studies (N = 484, 94% female), conducted in France, test and explore why racial prejudice and support for the death penalty (SDP) are strongly and positively related. First, prejudice against Arabs remains a significant predictor of SDP, even when ethnocentrism/authoritarianism (Study 1) and Right-Wing Authoritarianism (RWA; Study 2) are statistically controlled. Second, the attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 19 publications
6
48
1
Order By: Relevance
“…Given that SDO and RWA are known to have well-established and strong relationships to punitiveness and militarism via mechanisms unrelated to the ascription of ingroup characteristics (e.g., Cohrs, Moschner, Maes, & Kielmann, 2005;Dambrun, 2007), we expected any indirect effects through Whiteness to be relatively weak. Indeed, using Hayes' (2013) PROCESS macro, and controlling for all other variables, we found that Whiteness was a weak but significant mediator of the effects of SDO on each of harsh treatment (standardized indirect effect = .05; unstandardized indirect effect = .03, 95% CI = [.01, .06]) and militaristic counter-terrorism In sum, we observed strong support for our hypotheses: RWA and SDO each had significant and unique effects on the ascription of ingroup characteristics (i.e., Whiteness) to the Tsarnaev brothers-racially ambiguous targets suspected of committing a hugely norm-violating and reviled act, and thus posing a threat to group status and conformity.…”
Section: Resultsmentioning
confidence: 99%
“…Given that SDO and RWA are known to have well-established and strong relationships to punitiveness and militarism via mechanisms unrelated to the ascription of ingroup characteristics (e.g., Cohrs, Moschner, Maes, & Kielmann, 2005;Dambrun, 2007), we expected any indirect effects through Whiteness to be relatively weak. Indeed, using Hayes' (2013) PROCESS macro, and controlling for all other variables, we found that Whiteness was a weak but significant mediator of the effects of SDO on each of harsh treatment (standardized indirect effect = .05; unstandardized indirect effect = .03, 95% CI = [.01, .06]) and militaristic counter-terrorism In sum, we observed strong support for our hypotheses: RWA and SDO each had significant and unique effects on the ascription of ingroup characteristics (i.e., Whiteness) to the Tsarnaev brothers-racially ambiguous targets suspected of committing a hugely norm-violating and reviled act, and thus posing a threat to group status and conformity.…”
Section: Resultsmentioning
confidence: 99%
“…Four measures of prejudice were included: An eight-item scale of prejudice towards Arabs (Dambrun, 2007;a ¼ .78), 3 a six-item scale of prejudice towards prisoners (Bégin & Couture, 1980; a ¼ .70), a six-item scale of prejudice towards the poor (De Oliveira & Dambrun, 2007;a ¼ .59) and a new scale of prejudice towards Gypsies that we developed for this study (a ¼ .86). This last scale was composed of eight items: Four items had negative valences (e.g.…”
Section: Measures Of Prejudice Towards Disadvantaged Groupsmentioning
confidence: 99%
“…The results of Dambrun's (2007) study suggest that right-wing authoritarianism does not explain the relationship between racial prejudice and death penalty support. The author used the right-wing authoritarianism scale composed by Altemeyer (1988), which is believed to be a better measure of authoritarianism, in this study.…”
Section: Racist Punitive Bias Hypothesismentioning
confidence: 63%
“…In a series of three studies, Dambrun (2007), using path and regression analyses, tested whether racially prejudiced individuals support the death penalty as a means of punishing minority individuals who are perceived as being criminals and whether controlling for right-wing authoritarianism would affect the relationship between racial prejudice and death penalty support. Seven-point Likert scales were used to measure death penalty support, overall evaluation of Arab and black people (racial prejudice), and criminal traits attribution.…”
Section: Racist Punitive Bias Hypothesismentioning
confidence: 99%